Diagnostic and prognostic value of the HFA-PEFF score for heart failure with preserved ejection fraction: a systematic review and meta-analysis - Li, Xinmei; Liang, Yunyu; Lin, Xiaozhong (Frontiers in Cardiovascular Medicine, 2024)
Aim: To assess the diagnostic and prognostic performances of the Heart Failure Association Pre-test Assessment, Echocardiography & Natriuretic Peptide, Functional Testing, Final Etiology (HFA-PEFF) score for heart failure with preserved ejection fraction (HFpEF) in a comprehensive manner.Methods: PubMed, Embase, Cochrane Library, and Web of Science were comprehensively searched from the inception to June 12, 2023. Studies using the "Ruleout" or "Rule-in" approach for diagnosis analysis or studies on cardiovascular events and all-cause death for prognosis analysis were included. The Quality Assessment of Diagnostic Accuracy Studies (QUADAS-2) tool was adopted to assess the quality of diagnostic accuracy studies. The sensitivity (SEN), specificity (SPE), positive likelihood ratio (PLR), negative likelihood ratio (NLR), diagnostic odds ratio (DOR), and area under the summary receiver operating characteristic (SROC) curve (AUC) were presented with 95% confidence intervals (CIs). For CVEs and all-cause death, the hazard ratio (HR) values were calculated.Results: Fifteen studies involving 6420 subjects were included, with 9 for diagnosis analysis, and 7 for prognosis analysis. For the diagnostic performance of the HFA-PEFF score, with the "Rule-out" approach, the pooled SEN was 0.96 (95%CI: 0.94, 0.97), the pooled SPE was 0.39 (95%CI: 0.37, 0.42), and the pooled AUC was 0.85 (95%CI: 0.67, 1.00), and with the "Rule-in" approach, the pooled SEN was 0.59 (95%CI: 0.56, 0.61), the pooled SPE was 0.86 (95%CI: 0.84, 0.88), and the pooled AUC was 0.83 (95%CI: 0.79, 0.87). For the predictive performance of the HFA-PEFF score, regarding CVEs, the pooled SEN was 0.63 (95%CI: 0.58, 0.67), the pooled SPE was 0.53 (95%CI: 0.49, 0.58), and the pooled AUC was 0.65 (95%CI: 0.40, 0.90), and concerning All-cause death, the pooled SEN was 0.85 (95%CI: 0.81, 0.88), the pooled SPE was 0.48 (95%CI: 0.44, 0.52), and the pooled AUC was 0.65 (95%CI: 0.47, 0.83). A higher HFA-PEFF score was associated with a higher risk of all-cause death (HR 1.390, 95%CI 1.240, 1.558, P<0.001).The HFA-PEFF score might be applied in HFpEF diagnosis and all-cause death prediction. More studies are required for finding validation.